1985
DOI: 10.1037/0022-3514.49.5.1169
|View full text |Cite
|
Sign up to set email alerts
|

Social comparison in adjustment to breast cancer.

Abstract: We investigated four theoretical perspectives concerning the role of social comparison (Festinger, 1954) in coping with a threatening event in a sample of breast cancer patients. According to the supercoper perspective, personal contact with comparison others is often unavailable to patients, and contact with media "supercopers"--fellow victims presented as adjusting very smoothly--may make patients feel inadequate by comparison. According to the similarity perspective, patients select comparison targets who a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
359
4
4

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 515 publications
(383 citation statements)
references
References 19 publications
16
359
4
4
Order By: Relevance
“…This process has previously been described in a study of adjustment to breast cancer (Wood et al, 1985). Downward comparisons seemed to be most important early in the adjustment process, intended to prevent the victim from being overwhelmed by the frightening new circumstances (Wood et al, 1985). Another study of older people with cancer showed that downward comparisons were made mostly with persons in a worse state with regard to the effects and the old age itself, as a way to endure the cancer (Thomé et al, 2003).…”
Section: Discussion Of the Findingsmentioning
confidence: 93%
See 1 more Smart Citation
“…This process has previously been described in a study of adjustment to breast cancer (Wood et al, 1985). Downward comparisons seemed to be most important early in the adjustment process, intended to prevent the victim from being overwhelmed by the frightening new circumstances (Wood et al, 1985). Another study of older people with cancer showed that downward comparisons were made mostly with persons in a worse state with regard to the effects and the old age itself, as a way to endure the cancer (Thomé et al, 2003).…”
Section: Discussion Of the Findingsmentioning
confidence: 93%
“…This form of emotion-focused coping could be explained by "downward comparison", which is a cognitive process used to enhance subjective well-being by comparison with others whose condition is worse (Wills, 1981). This process has previously been described in a study of adjustment to breast cancer (Wood et al, 1985). Downward comparisons seemed to be most important early in the adjustment process, intended to prevent the victim from being overwhelmed by the frightening new circumstances (Wood et al, 1985).…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Individuals who had experienced job disruption (Pearlin, Lieberman, Menaghan, & Mullan, 1981), marital conflict (Menaghan, 1982), spinal cord injuries (Schulz & Decker, 1985), and general stressors (Pearlin & Schooler, 1978) rated their circumstances as more favorable than those of others. In an interview study, the vast majority of breast cancer patients spontaneously compared themselves with others who were less fortunate than they (Wood, Taylor, & Lichtman, 1985). For example, one woman said I had just a comparatively small amount of surgery on the breast, and I was so.miserable, because it was so painful.…”
Section: Target Selections Along the Dimension Under Evaluationmentioning
confidence: 99%
“…Goethals (1986a) pointed out, individuals fabricate and ignore social reality in ways that support a particular view oftbemselves. Thus, social comparison often may be a process of construction; it may not always involve comparisons with other people in any usual sense (Wood et al, 1985).…”
Section: The Active Social Comparermentioning
confidence: 99%
“…Moreover, people often engage in downward comparisons to feel better about themselves, especially when they feel threatened in their self-esteem (Wills, 1981). Failures and negative events appear under a more positive light when put in contrast to others who are worse off (Wood, Taylor, & Lichtman, 1985). In general, people engage in social comparison as a method of self-evaluation (Festinger, 1954;Kahneman & Miller, 1986;Mussweiler, 2003).…”
Section: Introductionmentioning
confidence: 99%